Data-driven business decisions - Lloyd, Chris J. (Statistics in practice., 2011)
A hands-on guide to the use of quantitative methods and software for making successful business decisions. The appropriate use of quantitative methods lies at the core of successful decisions made by managers, researchers, and students in the field of business. Providing a framework for the development of sound judgment and the ability to utilize quantitative and qualitative approaches, Data Driven Business Decisions introduces readers to the important role that data plays in understanding business outcomes, addressing four general areas that managers need to know about: data handling and Microsoft Excel(r), uncertainty, the relationship between inputs and outputs, and complex decisions with trade-offs and uncertainty.